Complication rate of different wound closures after primary hip arthroplasty - A survey of 373 patients - Yao Lu; Chengqiang Wang; Lijun Lin; Qingsong Qin; Qi Li (Elsevier, 2018)
Background: Wound closure is highly associated with wound complications and the best wound closure method was controversial in total hip arthroplasty. Methods: We performed a retrospective study of primary hip arthroplasty and compared three types of closure method. Results: 155 cases were closed using continuous subcuticular sutures then with staples, 111 using staples, 141 using interrupted sutures. 28 cases of wound complications occurred. Wound complication rates in subcuticular suture group, staple group and interrupted suture group were 1.9%, 11.7% and 8.5%, respectively (p < 0.01). Conclusion: Wound complication rate was significantly lower when wound was closed with continuous subcuticular suturue.